PRODUKSI BIBIT KELAPA KOPYOR TRUE-TO-TYPE MELALUI TEKNIK KULTUR EMBRYO - Sisunandar, Sisunandar (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Kopyor is one of the most valuable germplasm in Indonesia. However, the production of true-to-type seedlings with 100 % kopyor nuts is still limited because the nut would not germinated naturally. The only technique available to solve the problem is by using embryo culture technique. However, the technique is limited especially on the low of success rate after acclimatisation step (less than 40 %). Therefore, we report a new breakthough technique for producing kopyor seedling using embryo culture technique especially on acclimatisation step. Our results showed that the best acclimatisation step could be done by culturing 4-month old seedlings in a culture room with 14 hour light with intensity around 1400 lux and 10 hours in the dark. Seedlings were cultured for three months in mini growth chamber with 95 % relative humidity level and temperature around 26 to 28 0C. The survival rate after acclimatisation step on the seedlings with full root was more than 95 %, while for the seedlings without root was c.a 90 %. The acclimatized seedlings then underwent to screenhouse for 1 year befor being field planting. Up to now, more than 170 seedlings of Kopyor have been transfer to the field for developing seed garden of Kopyor in Purwokerto, Indonesia. In the future, creating a breeding program to produce hybrid of Kopyor will be useful for poverty reduction programmes in Indonesia.Â Keywords: acclimatization, growth chamber, hybrid of kopyor, seed genebank